The usefulness of presepsin in the early detection of anastomotic leakage after esophagectomy - Yoshiro Imai; Ryo Tanaka; Kentaro Matsuo; Hidero Yoshimoto; Mitsuhiro Asakuma; Hideki Tomiyama; Sang-Woong Lee (Surgery Open Science)
Background: Anastomotic leakage is a severe complication of esophagectomy, therefore early detection is crucial. Presepsin is a biomarker for early diagnosis of infectious complications. This study assessed presepsin as a biomarker for anastomotic leakage after esophagectomy, compared to C-reactive protein (CRP), white blood cells (WBCs), and neutrophils (Neuts). Materials and methods: This study enrolled 27 patients between October 2019 and December 2020. Levels of presepsin, CRP, WBCs, and Neuts were measured preoperatively and on postoperative days (PODs) 1, 3, 5, and 7. Results: Five patients had anastomotic leakage. Their presepsin levels on POD 7 were significantly higher and tended to be higher on POD 5 (p = 0.04 and p = 0.06, respectively) compared to those without leakage. The area under the curve values for presepsin were highest on PODs 5 and 7 (0.89 and 0.83). Optimal cut-off values for presepsin were 400 pg/mL (sensitivity 100 %; specificity 81.9 %) on POD 5 and similar on POD 7. Conclusions: Presepsin levels on PODs 5 and 7 effectively detect anastomotic leakage after esophagectomy, making it a valuable, simple, non-invasive early detection test.